Proceedings of the Scientific-Practical Conference "Research and Development - 2016" - Anisimov, K. V; Dub, A. V; Kolpakov, S. K; Lisitsa, A. V; Petrov, A. N; Polukarov, V. P; Popel, O. S; Vinokurov, V. A (Springer Nature, 2018)
This open access book relates to the III Annual Conference hosted by The Ministry of Education and Science of the Russian Federation in December 2016. This event has summarized, analyzed and discussed the interim results, academic outputs and scientific achievements of the Russian Federal Targeted Programme "Research and Development in Priority Areas of Development of the Russian Scientific and Technological  Complex for 2014-2020." It contains 75 selected papers from 6 areas considered priority by the Federal Targeted Programme: computer science, ecology & environment sciences; energy and energy efficiency; lifesciences; nanoscience & nanotechnology  and transport & communications. The chapters report the results of the 3-years research projects supported by the Programme and finalized in 2016.